PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. BANK WOORI SAUDARA INDONESIA 1906, Tbk (DIVISI CORPORATE SECRETARY) - Sumitra GP, Citra; Susilo, Herman (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
The purpose of this study was to determine the leadership style applied at PT Bank Woori Saudara Indonesia 1906, Tbk and to determine the influence of leadership style on employee performance at PT Bank Woori Saudara Indonesia 1906, Tbk. The method in this study is associative where the aim is to obtain information about the effect of leadership style on the performance of employees of the corporate secretary division at PT Bank Woori Saudara Indonesia 1906, Tbk. The author is interested in doing this research because leadership style is one of the important components in a company/organization. The research data source uses primary data obtained directly from respondents through interviews, data processing techniques using regression analysis with preparation stages, preparation of research plans, determination of research locations, implementation and reporting of research results. The results of the study based on the calculation of the simple linear regression equation in this study are as follows, Y = 5.030 + 0.927X. In this equation it can be seen that the leadership style (X) has a positive effect on the increase or decrease of the dependent variable, namely employee performance (Y). That the coefficient of determination (R Square) of 0.924 or 92.4% indicates that 92.4% of the dependent variable, namely employee performance (Y), can be explained by the leadership style policy. leadership (X) while the remaining 7.6% is a variable not examined in this research model. Because leadership style has a very strong relationship to employee performance, the leadership style must be given more attention by the company because this can improve employee performance so that they can make the best contribution to the company.